O023 Impact of weight loss of OSA pathophysiology. (7th October 2021) - Wong, A; Landry, S; Yang, K; Joosten, S; Thomson, L; Mansfield, D; Sands, S; Patel, S; Cistulli, P; Sutherland, K; Hamilton, G; Edwards, B
Abstract: Introduction: Obesity is a major risk factor for developing obstructive sleep apnoea (OSA), however, the underlying mechanisms are not fully understood. We aimed to assess the impact of weight loss on all OSA endotypes (i.e. upper airway collapsibility, muscle compensation, respiratory arousal threshold, and loop gain). Methods: We analysed data from 40 OSA patients (collated from 3 centres) who underwent bariatric surgery. Demographics and clinical polysomnograms (PSG) were performed at baseline and at between 6–18 months post-surgery. OSA endotypes were measured during sleep using non-invasive endotyping methods (derived from clinical PSG). Results: Participants lost 28±14 kg and had a post-surgery reduction in the AHI of 19.6 (Interquartile range[IQR] -9.8 to -35.4) events/hr [from baseline 39.9 (24.3 to 65.6) events/hr to 17.0 (9.9 to 33.3) events/hr]. Following surgical weight loss, there was significant improvement in collapsibility (∆6.2 [IQR -1.4 to 13]%Veupnoea, p<0.0001), as well as significant reduction in loop gain and arousal threshold (∆-0.06 [-0.17 to 0.009], p<0.001 and ∆-13.7 [-24.8 to -1.8]%Veupnoea, p<0.001 respectively). There was no significant change in muscle compensation. Conclusion: Our findings suggest that weight loss improves upper airway collapsibility and reduces loop gain and the arousal threshold, providing novel insights about the mechanisms by which obesity causes OSA. Further analysis is underway to determine whether knowledge of the baseline OSA endotypes (in isolation and/or in combination) can predict which individuals will have a response to weight loss alone.